Stimulating Online Purchase Intentions Through Digitalization: Intermediation of Perceptions and Electronic Word of Mouth in Fashion E-commerce (Journal of Asian Development Studies, 2025)
The present study adopts a holistic approach to studying the effect of digital marketing on online purchase intentions in the fashion industry in Pakistan. It highlights the intermediating role of electronic word of mouth between digital marketing-driven purchase intentions. We adopted to understand this phenomenon followed by quantitative research design and incorporated quantitative design. For data collection, we targeted 302 urban online consumers from Karachi based on convenience sampling. Our research framework included casual constructs such as social media marketing, content marketing, perceived ease of use, and perceived usefulness, and we examined their impact on online purchase intentions. We analyzed primary data with a partial least square structural equational modeling technique. The findings provided meaningful insights that infer that digital marketing strategies may be used as a tool to trigger online purchase intentions, particularly in the fashion industry in Pakistan. Furthermore, electronic word of mouth serves the bridging role between digital strategies and purchase intentions, reflecting on sales and marketing policy dedicated to nourishing the online shopping behavior in the fashion industry in Pakistans. Overall, we propose that digital marketing strategies enhance online purchase intentions in the fashion industry by sharpening perceptions and boosting the impact of electronic word of mouth.